LEGAL PROTECTION AND WELFARE IN EDUCATION: A POST-PANDEMIC RECOVERY PERSPECTIVE ON IMPLEMENTING LAW NO. 14 OF 2005 - Wartoyo, Franciscus Xaverius; Prasetyo, Teguh (Jurnal Pembaharuan Hukum, 2023)
Legal protection for teachers and lecturers in the post-COVID-19 pandemic period needs to be pursued, because it is part of improving their welfare in addition to safety in every activity and task. As referred to in article 14 paragraph (1) point e "Law No. 14 of 2005 concerning Teachers and Lecturers which includes legal protection, professional protection, occupational safety and health protection, and intellectual property rights (IPR)". This study intends to describe how the development of education in the implementation of Law No. 14 of 2005 concerning Teachers and Lecturers is viewed from the rights and obligations in the perspective of dignified justice. Research methods used normatively and empirically and literature review that supports descriptive exposure to strengthen argumentation and persuasion that explains facts in the field and the results of relevant data collection from various applicable legal sources. The COVID-19 pandemic has ended with Presidential Decree No. 17 of 2023, but the impact felt on teachers and lecturers, especially private universities, is still being felt today. The duties of teachers or lecturers, both public and private, have the same duties, it's just that the obligations are different, where it is determined by the conditions of each institution that houses the public and private. The task of the state in this case is that policy makers who oversee the education and private sectors through  their corporate social responsibility (CSR) would be nice to facilitate and support the duties of teachers and lecturers, because the duties of teachers and lecturers have the same duties, but judging from private universities in their operational management is still determined by the foundation of the university, especially related to the tri dharma of higher education and needs to be considered The welfare of its human resources, thus as a suggestion to pay more attention to supporting the welfare of human resources of private universities, land and building tax subsidies, electricity subsidies, rewards for authors of the Scopus journal, Sinta, or special grants for private universities, in order to restore the management of private universities, especially financial management operations so that they can compete with state universities. In implementing Law No. 14 of 2005 concerning Teachers and Lecturers, especially in the post-COVID-19 pandemic, private educational institutions are expected to get special attention and for private educational institutions the impact is very influential, especially in the field of financial management, in order to harmonize their financial management as before the COVID-19 pandemic, especially for teachers and lecturers who obtain welfare from private educational institutions in order to harmonize rights and obligations as stated in Law no. 14 of 2005 and realizing alenia 4 "educating the life of the nation" NRI Constitution 1945 and Pancasila which are justice-oriented with an intention.